PERAN ORGANISASI REMAJA MASJID DALAM PENGUATAN PEMAHAMAN KONSEP PAI DI SMP NEGERI 19 SURABAYA - Khoirun Nisa’ir Rofi’ah; Muhammad Fahmi; Ali Mas'ud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The education in Indonesia is currently experiencing enormous problems due to the spread of Covid 19, The Indonesian education paradigm emphasizes holistic development through PAI, but formal learning often over-focuses on theoretical cognitive aspects. This study examines how the Mosque Youth Organization (Remaja Masjid) at SMPN 19 Surabaya bridges this gap. Using a qualitative case study , the research investigates the process of transforming affective experiences into cognitive understanding of PAI material. Findings show Remaja Masjid acts as both a practical facilitator and an incubator for religious leaders. Crucially, the organization generates a positive affective climate where enthusiasm stimulates intellectual curiosity (rasa ingin tahu). This motivation leads to voluntary and deeper cognitive learning of PAI concepts. The organization primarily functions as an accelerator for students already possessing a basic religious foundation, enhancing their existing potential.